Neural signature of human–dog interactions: EEG correlates from comparisons with plant and replica dog in a within-subject, cross-over randomized trial - Carbone, Fabio; Martin-Grieder, Caroline; Hediger, Karin (Frontiers in Human Neuroscience, 2026)
BackgroundHuman–dog interactions (HDIs) are widely associated with emotional and physiological benefits, yet their neural underpinnings remain poorly understood. This study investigated cortical oscillatory dynamics during HDI compared to two control conditions: interacting with a plant and a realistic dog replica.MethodsIn a within-subject, cross-over randomized design, 29 healthy adults participated in three EEG sessions, each including all conditions. EEG power spectral density was analyzed across theta (4–8 Hz), alpha (8–13 Hz, including slow and fast sub-bands), and beta (13–30 Hz, including low and mid sub-bands) frequencies from 10 electrodes covering prefrontal, frontal, central, parietal, and occipital regions.ResultsOur observations revealed distinct neural signatures for HDI. Compared to plant and replica conditions, dog interaction was characterized by reduced alpha power, particularly in occipital and parietal sites, suggesting increased attentional engagement. Beta power was enhanced in frontal and central electrodes during dog interaction, reflecting heightened cognitive processing and sensorimotor readiness. Theta activity showed regional differences, with lower occipital theta power during HDI relative to controls, indicative of externally oriented attention. By contrast, the replica dog occasionally elicited increased beta and theta power, suggesting compensatory or evaluative processing of ambiguous stimuli.ConclusionThese findings provide novel electrophysiological evidence that interacting with a real dog elicits unique oscillatory patterns distinct from those observed with non-sentient—living or non-living—controls. The results highlight the social and emotional salience of animals and advance understanding of the neurocognitive mechanisms underlying human–animal interactions, with implications for applied contexts such as animal-assisted treatments.